Effects of chitosan-containing silver nanoparticles or chlorhexidine as the final irrigant on the bond strength of resin-based root canal sealers - Berkan Celikten; Gulin Amasya; Aysenur Oncu; Mehrdad Koohnavard; Feridun Saklar (Journal of Dental Research, Dental Clinics, Dental Prospects, 2022)
Background. This study evaluated the combined effects of silver nanoparticles (AgNPs) and chitosan on the dentin bond strength of resin-based root canal sealers using the push-out test and scanning electron microscopy (SEM). Methods. This in vitro study was conducted on 72 extracted mandibular premolar teeth. All the teeth were decoronated perpendicular to the long axis to leave a 13-mm root length. The root canals were prepared, and the samples were randomly divided into seven experimental groups and one control group based on final irrigation solutions. All the final irrigation procedures were performed for one minute. The root canals were dried using paper points and filled with a resin-based sealer and gutta-percha points using a lateral condensation technique. Sections measuring 2 mm in thickness were taken from the apical, middle, and coronal thirds of each root using a cutting machine. The push-out test was performed using a universal testing machine. Results. The solution of AgNPs combined with 0.4% chitosan showed higher bond strength in the coronal region than a combination with 0.2% chitosan. Samples treated with 0.4% chitosan solution exhibited a higher bond strength than the 0.2% chitosan group. There were no significant differences between chlorhexidine (CHX) solution alone and in combination with 0.2% or 0.4% chitosan solution. Conclusion. The combination of chitosan and AgNPs was as effective as CHX in improving the bond strength of resin-based sealers.